Analisis Keberadaan Go Food Dan Grab Food Terhadap Peningkatan Penjualan Usaha Kuliner Di Kelurahan Kekalik Jaya Kota Mataram - Mimi Cahayani (Universitas Hamzanwadi, 2021)
The development of technology and information plays an important role in economic growth. Today, technology and information are needed, including in the culinary business. The presence of Go Food and Grab Food services, which are a food delivery feature for food delivery messages developed by the Gojek and Grab applications, is very helpful for culinary entrepreneurs in running their business. This study aims to determine how Go Food and Grab Food exist, how to increase sales of culinary businesses in Kekalik Jaya Village, Mataram City after joining Go Food and Grab Food. This research uses descriptive qualitative research methods. Data collection was carried out through interviews with culinary entrepreneurs in Kekalik Jaya Village, Mataram City. The results show that the existence of Go Food and Grab Food is very helpful for culinary entrepreneurs in the form of marketing and increasing sales. Culinary business people stated that there was an increase in sales after joining Go Food and Grab Food services